Exploration of the Use of Digital Learning Videos in Facilitating Students' Cognitive Analysis Transformation on the Food Chain Material: A Case Study at State Elementary School 2 Sukatani Garut - Novi Daniyati; Uman Suherman AS; Galih Abdul Fatah Maulani (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study aims to explore the use of digital learning videos in facilitating cognitive transformation of student analysis on food chain material at State Elementary School 2 Sukatani. The study used a qualitative approach with a case study method. The research subjects consisted of fifth grade students, class teachers, and learning documents. Data collection techniques were carried out through observation, in-depth interviews, and document analysis. Data analysis used the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results of the study showed that: (1) digital learning videos were able to increase student cognitive engagement through concrete visualization of the food chain concept; (2) there was a cognitive transformation from the level of understanding to analysis which was characterized by students' ability to identify relationships between ecosystem components; and (3) supporting factors included the quality of video content, teacher pedagogical strategies, and discursive interactions in the classroom. However, there were obstacles in the form of limited facilities and variations in students' digital literacy abilities. (4) Teachers' strategies in optimizing the use of digital learning videos lie not only in media selection, but in how the media is integrated in a systematic, interactive learning process, and oriented towards developing students' higher-order thinking skills.